Knowledge-based approach for stretch blow molding - Ali, Mohammad Yeakub; Bohez, E. L. J. (2000)
The general principle of stretch blow molding is easy to describe but in practice it requires considerable knowledge and skill. Currently people apply their own knowledge gained through a blend of experience, intuition, and guesswork. As a result, there could be different solutions proposals for the same problem. Furthermore, it is not unusual to propose different solution at different times for the same problem. The stretch blow molding process, like other manufacturing processes, appears to be an appropriate domain for knowledge-based system (KBS) development. A KBS was developed to aid the designer for the selection of resin, design of preform and container, and processing. The KBS contains about 200 production rules. A guided forward chaining concept is used for inferencing. The user needs to input the basic requirements such as volume of the container, end use, etc for a systematic advice.